EFEKTIVITAS KAMPUNG KELUARGA BERKUALITAS UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN BADUNG - Nuryati, Ni Gusti Ayu Putri (Universitas Tabanan, 2025)
This research focuses on the issue of the still high and continuously increasing population growth rate in Badung Regency, Bali Province, as well as the suboptimal implementation of the Kampung KB (Quality Family Village) program in Badung Regency. The objectives of this study are to determine the effectiveness of the Kampung KB program in Badung Regency, Bali Province; to identify the inhibiting factors affecting the effectiveness of the Kampung KB program in controlling the population growth rate in Badung Regency, Bali Province; and to understand the efforts made to improve the effectiveness of the Kampung KB program in controlling the population growth rate in Badung Regency, Bali Province. This research uses a descriptive method with an inductive approach, analyzed using Duncan’s theory of effectiveness. The data collection techniques employed are interviews, observation, and documentation, with data analysis techniques including data reduction, data presentation, and conclusion drawing. The results of the research indicate that the Kampung KB program has been effective in controlling the population growth rate in Badung Regency, Bali Province. However, several obstacles remain, such as the insufficient quantity and quality of extension workers and the lack of supporting infrastructure and facilities for the Kampung KB program. The DP3AP2KB (Office of Women's Empowerment, Child Protection, Population Control and Family Planning) has taken several steps, such as increasing the number of extension workers and allocating budgets to improve the infrastructure and facilities of the Kampung KB program. The results of this study show that although the Kampung KB program has been effective in controlling population growth, there are still challenges such as the lack of extension workers and inadequate facilities and infrastructure. The efforts made by DP3AP2KB to address these obstacles include increasing the number of extension workers and allocating funds to improve facilities and infrastructure. Keywords : effectiveness, Kampung KB, community welfare